2008
DOI: 10.1016/j.ijsolstr.2007.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Bleustein–Gulyaev wave in 6mm piezoelectric materials loaded with viscous liquid

Abstract: The influence of a viscous liquid on acoustic waves propagating in elastic or piezoelectric materials is of particular significance for development of liquid sensors. Bleustein-Gulyaev wave is a shear-type surface acoustic wave and has the advantage of not radiating energy into the adjacent liquid. These features make the B-G wave sensitive to changes in both mechanical and electrical properties of the surrounding environment. The Bleustein-Gulyaev wave has been reported to be a good candidate for liquid sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 9 publications
3
38
0
Order By: Relevance
“…It is well known that piezoelectric materials are widely used in acoustic wave devices such as sensors, actuators, and transducers for their strong coupling between electric and mechanical constitutive behavior since White invented the interdigital transducers utilized for transmitting and receiving surface acoustic waves in 1965 [5]. There are numerous investigations have been taken on SH-SAWs in piezoelectric media due to their extensive applications [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that piezoelectric materials are widely used in acoustic wave devices such as sensors, actuators, and transducers for their strong coupling between electric and mechanical constitutive behavior since White invented the interdigital transducers utilized for transmitting and receiving surface acoustic waves in 1965 [5]. There are numerous investigations have been taken on SH-SAWs in piezoelectric media due to their extensive applications [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The sensors utilizing surface acoustic waves (SAW) are superior to the conventional BAW devices in liquid sensor applications since SAW devices can operate at much higher frequencies and more mass sensitive since SAW possesses large attenuation and energy loss due to a mode conversion in the liquid and dissipates due to the viscous effects [15]. Guo & Sun [19] found that shear type SAW is a good candidate for liquid sensing applications. Other alternative to the SAW presented was the shear horizontal (SH) surface wave as seen in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Equivalently, the speed of a propagating wave in a body in contact with a fluid is also affected by the fluid. This effect has been used to make various fluid sensors for measuring fluid viscosity or density (Kanazawa & Gordon, 1985;Josse et al, 1990;Reed et al, 2001;Kim et al, 1991;Vogt et al, 2004;Guo & Sun, 2008;Peng et al, 2006). More references can be found in a review article (Benes et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For fluid sensor applications, vibration modes of a body without a normal displacement at its surface are of general interest. Thickness-shear and thickness-twist modes in a plate (Kanazawa & Gordon, 1985;Josse et al, 1990;Reed et al, 2001), torsional modes of a circular shaft (Kim et al, 1991;Vogt et al, 2004), and anti-plane surface waves (Guo & Sun, 2008;Peng et al, 2006) are modes with tangential surface displacements only and have been used for fluid sensor applications. To establish the relation between wave frequency and fluid density or viscosity, a coupled problem of fluid-structure interaction needs to be solved.…”
Section: Introductionmentioning
confidence: 99%